Pengembangan Data Geospasial Melalui Pemetaan Desa Dengan Menggunakan Drone Di Kelurahan Pondidaha Kabupaten Konawe - Karim, Jufri; Salihin, L.M. Iradat; Saleh, Fitra; Hidayat, Ahmad; Khairisa, Noor Husna (Edumedia Solution, 2023)
Geospatial data is indispensable as basic information for resource utilization and area development. Geospatial data in the form map is necessary to be owned by each administrative area until smallest unit (village/kelurahan). However, the availability of geospatial data in the village is still very limited so that information about the geographical conditions and potentials of the village is not thoroughly known. Administratively, Pondidaha Kelurahan is included in the Pondidaha Sub-district, Konawe Regency, but does not have sufficient geospatial data yet to describe the geographical condition of the area. Therefore, the community service team together with apparatus and community of Pondidaha compiled geospatial data in the Pondidaha by using drone. The activities were started from the collection of secondary data as initial and supporting data in field activities, then continued by coordination with government and community of Pondidaha. Making geospatial data using drones is done by these following steps: (1) making work maps; (2) identifying, validating and field mapping; (3) processing GCP/ICP control point data; (4) processing aerial photography data; (5) making digital land maps; (6) compiling spatial databases; (7) cartographic and printing processes. Geospatial data generated include: landform map, topographical map, slope map, administrative map and land use map of Pondidaha.